1982
DOI: 10.1088/0031-9120/17/5/002
|View full text |Cite
|
Sign up to set email alerts
|

Energy and its carriers

Abstract: Reports on the first course of a new physics curriculum developed at the Karlsruhe Institute for the Didactics of Physics (Falk and Herrmann 1977, 1978, 1979, 1981). The entire curriculum begins at the elementary school level with children aged 10-12 and is intended to extend beyond high school and through university studies (Falk and Ruppel 1975, 1976). Energy is introduced as the primary quantity at the very beginning of the course. It is not 'derived' from other seemingly more fundamental quantities such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…A more comprehensive attempt to conceive of a continuous learning trajectory between the naïve and scientific concept of energy has involved a proposal to reconceptualize the scientific concept itself as a substance-like entity for pedagogical purposes [Duit, 1987;Schmidt, 1982]. Schmidt [1982] reports on a comprehensive approach to teaching physics from this perspective.…”
Section: Science Education Research On Learning and Teaching The Concmentioning
confidence: 99%
See 1 more Smart Citation
“…A more comprehensive attempt to conceive of a continuous learning trajectory between the naïve and scientific concept of energy has involved a proposal to reconceptualize the scientific concept itself as a substance-like entity for pedagogical purposes [Duit, 1987;Schmidt, 1982]. Schmidt [1982] reports on a comprehensive approach to teaching physics from this perspective.…”
Section: Science Education Research On Learning and Teaching The Concmentioning
confidence: 99%
“…Schmidt [1982] reports on a comprehensive approach to teaching physics from this perspective. In this approach, energy is seen as a substance-like entity that: can be contained and thereby stored in some system; can flow from some source to a receiver; this flow is via some other substance-like entity which can be referred to as a 'carrier'; when a substance is received into some con-tainer it can then function as a source, thereby functioning as a point in a chain of energy exchanges.…”
Section: Science Education Research On Learning and Teaching The Concmentioning
confidence: 99%
“…Indeed, in both its everyday use and the way it is used in many school textbooks, the term is much closer in meaning to the scientific concept of free energy than the concept of energy. This has caused much confusion and stimulated a great deal of debate about these issues (e.g., Duit, 1981;Schmid, 1982;Warren, 1982;Marx, 1983;Driver & Millar, 1986;Ellse, 1988;Ross, 1988;Solomon, 1992). Research into children's ideas about energy suggests that their starting point is that energy represents a power to act which is used up and may be refreshed (e.g., Watts, 1983;Solomon, 1984).…”
Section: About the Approachmentioning
confidence: 99%
“…He discussed proposals by some science education scholars like Duit [1987] and Schmidt [1982] to teach the scientific concept of energy as a substance-like entity in order to close the gap between students' initial conceptions of energy and the abstract, mathematical concept of energy, and the limitations of such an analogy-based approach [e.g., Lijnse, 1990;Warren, 1982Warren, , 1986. He suggested that conceptual metaphor theory can provide insights about how to bootstrap the scientific concept, based on the finding of his analysis that showed a multiplicity of metaphors used to talk about energy in science discourse.…”
mentioning
confidence: 99%